2013
DOI: 10.1139/apnm-2012-0286
|View full text |Cite
|
Sign up to set email alerts
|

The ergogenic effect of beta-alanine combined with sodium bicarbonate on high-intensity swimming performance

Abstract: We investigated the effect of beta-alanine (BA) alone (study A) and in combination with sodium bicarbonate (SB) (study B) on 100- and 200-m swimming performance. In study A, 16 swimmers were assigned to receive either BA (3.2 g·day−1 for 1 week and 6.4 g·day−1 for 4 weeks) or placebo (PL; dextrose). At baseline and after 5 weeks of supplementation, 100- and 200-m races were completed. In study B, 14 were assigned to receive either BA (3.2 g·day−1 for 1 week and 6.4 g·day−1 for 3 weeks) or PL. Time trials were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
64
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 34 publications
(54 reference statements)
6
64
1
4
Order By: Relevance
“…This agrees with the very limited evidence from studies on the effects of beta-alanine supplementation on swimming performance. Chung et al (2012) found no clear effect of 10 wk of supplementation on performance in elite and subelite swimmers, though de Salles Painelli et al (2013) reported significant improvements in 200-m swim performance and a trend toward an improvement in a 100-m swim after 5 wk of supplementation. It is worth noting that, although the improvement in performance was reported not to be statistically significant, all nine swimmers recorded faster times after supplementation, and four of seven in the placebo group swam faster.…”
Section: Bicarbonate and Beta-alaninementioning
confidence: 95%
See 1 more Smart Citation
“…This agrees with the very limited evidence from studies on the effects of beta-alanine supplementation on swimming performance. Chung et al (2012) found no clear effect of 10 wk of supplementation on performance in elite and subelite swimmers, though de Salles Painelli et al (2013) reported significant improvements in 200-m swim performance and a trend toward an improvement in a 100-m swim after 5 wk of supplementation. It is worth noting that, although the improvement in performance was reported not to be statistically significant, all nine swimmers recorded faster times after supplementation, and four of seven in the placebo group swam faster.…”
Section: Bicarbonate and Beta-alaninementioning
confidence: 95%
“…De Salles Painelli et al (2013) looked at the independent and additive effects of bicarbonate and beta-alanine supplementation on 100-m and 200-m swim performance and found that both bicarbonate and beta-alanine supplementation improved 100-and 200-m swimming performance. The coingestion of beta-alanine and bicarbonate induced a further, albeit nonsignificant, improvement in performance.…”
Section: Bicarbonate and Beta-alaninementioning
confidence: 99%
“…This pre-exercise increase in blood pH can delay the rapid decrease in blood pH induced by sprint exercise. Many studies using pre-exercise supplementation with bicarbonate ions to increase pre-exercise blood pH and buffer capacity have reported significantly higher performance compared to control [1]. More recently, some authors also reported that sodium bicarbonate ingestion positively affected repeated swim sprint performance [1].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies using pre-exercise supplementation with bicarbonate ions to increase pre-exercise blood pH and buffer capacity have reported significantly higher performance compared to control [1]. More recently, some authors also reported that sodium bicarbonate ingestion positively affected repeated swim sprint performance [1]. However, some others do not report any significant improvements in performance after NaHCO 3 ingestion [1].…”
Section: Introductionmentioning
confidence: 99%
“…Results have been mixed, with additive benefits reported for upper-body intermittent performance [133] and small non-significant but likely increases in performance reported in cycle capacity [116,162], 2000m rowing [242] plus 100 m and 200m swimming [120]. Other studies have reported no additive benefit for cycle capacity [4] and RSA during cycling and running [4,146,238].…”
Section: Introductionmentioning
confidence: 99%